Portal venous injection in the rat. Issue 7 (July 1971) - Blumgart, L. H.; Leach, K. G.; McLachlan, M. S. F.; Seager, S.; Ryan, C. J.
Abstract : A technique for subcutaneous transposition of the spleen in the rat is described. The preparation has been developed as a reliable means of transplenic portal injection. It has been shown that different substances injected into the pulp of the transposed spleen are cleared and not pooled in the organ. The development of porta-systemic venous communications has been demonstrated and their detection radiologically and by isotope techniques is illustrated. It is suggested that the technique outlined in this communication may be of value in the study of the portal circulation, the function of the liver, and in the investigation of drug action. If adequate porta-systemic venous connexions are present the portal vein can be tied above its splenic tributary and the animal will survive. The method offers a simple means of porta-systemic diversion in the rat.